Models of making decisions to select the techniques for countering innovative project risks - Kosenko, V. (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter of the study is the risks of an innovative project. The goal of the article is to develop models of making decisions to select the techniques for countering innovative project risks. The following tasksare solved in the article: the features of managing innovative project risk are analyzed, a generalized model of the project risk management is developed, the mechanisms to counter the innovative risks are analyzed, a decision tree is developed to select the technique to counter innovative project risks, a formalized method and a process model are developed to select a preferred technique for risk insurance. The following methodsare applied – system analysis, project approach, risk-based approach, heuristic decision-making methods, process models. The following resultsare obtained: the analysis of the features of managing innovative project risks showed the possibility of reducing the cost of risk by modern techniques ofcountering financial risks, including insurance in its various forms. A generalized model of managing innovative project risks is proposed; this model includes the stages of developing possible measures to counter risks and making decisions on selecting the preferred option. The probable types of innovation project risks, methods of their assessment under uncertainty are considered. The techniques to counter innovation risks, including the types of project risk insurance, are analyzed.A decision tree is developed to select a technique for countering risk based on a number ofits characteristics that are defined according to the qualitative and classification scale. The suggested technique is formalized for selecting a mechanism to insure project risks, taking into account the probabilities of specific risks, their costs and the general insurance fund of a project. A process model is developed to select the preferred technique of insurance, taking into account the integral assessment of an innovation risk. Conclusions. The use of the developed models while planning the risk management of an innovative project increases the validity and reliability of decisions concerning the selection of a technique for countering risks, taking into account the characteristics of specific risks, the magnitude of the integral risk and the features of a particular project.

Предметом дослідження в статті є ризики інноваційного проекту. Мета статті – розробка моделей процесів прийняття рішень для вибору способів парирування ризиків інноваційного проекту. Завдання, які вирішуються: аналіз особливостей управління ризиками інноваційного проекту, розробка узагальненої моделі процесу управління ризиками проекту, аналіз механізмів парирування інноваційного ризику, розробка дерева рішень для вибору способу парирування ризиків інноваційного проекту, розробка формалізованого методу і процесної моделі вибору кращого способу страхування ризику. Застосовувані методи: системний аналіз, проектний підхід, ризик-орієнтований підхід, евристичні методи прийняття рішень, процесні моделі. Отримані результати. Проведений аналіз особливостей управління ризиками інноваційного проекту показав можливість зниження вартості ризиків шляхом застосування сучасних методів парирування фінансових ризиків, в тому числі страхування в різних його формах. Пропонується узагальнена модель процесу управління ризиками інноваційного проекту, яка включає етапи вироблення можливих заходів щодо парирування ризиків і прийняття рішення щодо вибору кращого варіанту. Розглянуто можливі види ризиків інноваційного проекту, методи їх оцінки в умовах невизначеності. Проаналізовано механізми парирування інноваційних ризиків, в тому числі і види страхування ризиків проекту. Сформовано дерево рішень по вибору способу парирування ризику на основі ряду його характеристик, визначених у якісній і класифікаційній шкалах. Формалізовано представлений метод вибору механізму страхування ризиків проекту з урахуванням ймовірностей часткових ризиків, їх вартості та загального страхового фонду проекту. Розроблено процесну модель вибору кращого способу страхування з урахуванням інтегральної оцінки інноваційного ризику. Висновки. Застосування розроблених моделей в плануванні процесів управління ризиками інноваційного проекту підвищує обґрунтованість і достовірність рішень по вибору способу парирування ризиків шляхом урахування характеристик часткових ризиків, величини інтегрального ризику та особливостей конкретного проекту.
Моделі процесів прийняття рішень з вибору способів парирування ризиків інноваційного проекту
Keywords: risk probability; risk countering techniques; risk insurance; ймовірність ризику; методи парирування; страхування